Optimizing surface active sites via burying single atom into subsurface lattice for boosted methanol electrooxidation - Yunxiang Lin; Bo Geng; Ruyun Zheng; Wei Chen; Jiahui Zhao; Hengjie Liu; Zeming Qi; Zhipeng Yu; Kun Xu; Xue Liu; Li Yang; Lei Shan; et al. (Nature Communications)
Abstract The precise fabrication and regulation of the stable catalysts with desired performance still challengeable for single atom catalysts. Here, the Ru single atoms with different coordination environment in Ni3FeN lattice are synthesized and studied as a typical case over alkaline methanol electrooxidation. The Ni3FeN with buried Ru atoms in subsurface lattice (Ni3FeN-Ruburied) exhibits high selectivity and Faradaic efficiency of methanol to formate conversion. Meanwhile, operando spectroscopies reveal that the Ni3FeN-Ruburied exhibits an optimized adsorption of reactants along with an inhibited surface structural reconstruction. Additional theoretical simulations demonstrate that the Ni3FeN-Ruburied displays a regulated local electronic states of surface metal atoms with an optimized adsorption of reactants and reduced energy barrier of potential determining step. This work not only reports a high-efficient catalyst for methanol to formate conversion in alkaline condition, but also offers the insight into the rational design of single atom catalysts with more accessible surficial active sites.